Relation of Pre-operative Ureteral Catheter Use and Complications of Intraoperative Ureteral and Bladder Trauma in Gynecologic Oncology Patients Undergoing Major Surgical Procedures - Sinurat, Bintang; Toreh, Christof; Astram, Ari; Arianto, Eko; Langi, Fima (Medical Scope Journal, 2025)
Iatrogenic injury to the urinary tract is a potential complication of all surgical procedures performed in or retroperitoneum and pelvis. Gynecological surgery in particular has a risk of urinary tract injury due to the close anatomy of the urinary tract and the reproductive system in women. This study aimed to evaluate the relation between pre-operative ureteral catheter use and complications of intraoperative ureteral and bladder trauma in gynaecologic oncology patients undergoing major surgical procedures. This study used cohort data of patients undergoing major surgical procedures at Prof. Dr. R. D. Kandou Hospital, Manado, recorded in medical records from January 1, 2023 to June 30, 2023. The bivariate test showed that patients who received pre-operative ureteral catheter insertion had fewer urological trauma events (4.5%) compared to patients who did not get pre-operative ureteral catheter (95.5%). The relations between pre-operative ureteral catheters and the incidence of urological trauma was found to be statistically significant with a p-value of 0.019 and the history of chemotherapy had a p-value of 0.036, meanwhile the relations with other variables showed p-values of >0.05. Therefore, the use of pre-operative catheters could not significantly eliminate the occurrence of ureteral trauma because many of the confounding factors were accompanied by several other conditions that were also studied in the multivariate analysis. In conclusion, there is no association between the use of pre-operative ureteral catheters and complications of intraoperative ureteral trauma in gynecologic oncology patients undergoing major surgical procedures. Future studies using samples from more sources are expected to assess the relation between pre-operative ureteral catheter use and the incidence of urological trauma more accurately, and to assess the ease of use of pre-operative ureteral catheter. Keywords: ureteral catheter; ureteral trauma; gynaecologic oncology patients